Identifikasi Bahaya dan Penilaian Risiko Kebakaran dengan Metode Fire Risk Assessment pada PT Aneka Gas Industri Tbk, Bekasi - Agustina, Agustina; Pramesti, Regina Intan (Jurnal Persada Husada Indonesia, 2021)
Hazard identification process is one part of risk management. Risk assessment is a process to determine the priority of control over the level of risk of accidents or occupational diseases. Hazard identification process can be started by group. Fire Risk Assessment (FRA) is a process for describing risks associated with fires discussing the fire scenario or scenarios of concern, their probabilities, and potential consequences. The purpose of this study was to determine "identification of hazards and assessment of fire risk with the method of fire risk assessment". This research design is semi-qualitative with a case study approach. The focus of the research is fire risk assessment. The research was conducted from May-August 2021. Purposive sampling as an informant was taken. The number of informants is 4 people, namely: informant1 (SHE officer), informant 2 (Supervisor area ASP), informant 3 (Maintenance), informant 4 (Filling area operator). Data taken through in-depth interviews, observation and document review. Data analysis using triangulation. Fire hazard identification: There is training available for workers according to their field of work and fire emergency response training. There are policies related to fire prevention and control. Regarding the use of combustible raw materials in the production process and has implemented the storage of combustible raw materials properly and separately. The company has a fixed procedure in the form of a checklist. The company produces waste storage. The waste is stored separately. Fire risk assessment: using 3 methods, namely a. Fire risk assessment (FRA) in the air separation plant (ASP) area, there are 5 types of activities, b. Fire risk assessment (FRA) in the filling station area there are 4 types of activities and c. the fire risk assessment (FRA) method in the travo and genset area there is one activity.